Chemical Composition and Assessment of the Anti-Inflammatory, Antioxidant, Cytotoxic and Skin Enzyme Inhibitory Activities of Citrus sinensis (L.) Osbeck Essential Oil and Its Major Compound Limonene - Naoufal El Hachlafi; Amine Elbouzidi; Amine Batbat; Mohamed Taibi; Mohamed Jeddi; Mohamed Addi; Hanae Naceiri Mrabti; Kawtar Fikri-Benbrahim (Pharmaceuticals)
Background/Objectives: Essential oils (EOs) from Citrus species have attracted attention for their diverse properties, including anti-inflammatory, antioxidant and cytotoxic effects, which address critical health challenges such as chronic diseases and skin disorders. Citrus sinensis (L.) Osbeck, which is a widely cultivated citrus fruit, is attracting increasing attention in the field of medicinal research due to its richness of limonene (comprising approximately 85–90% of the oil). This study investigates the chemical profile of CS-EO and biological activities of CS-EO and limonene. Methods and Results: This study used gas chromatography–mass spectrometry (GC-MS), confirming limonene as the predominant compound (70.15%) along with other minor constituents, including thujene (10.52%), myrcene (5.54%) and α-pinene (2.81%). The biological activities of CS-EO and limonene were examined, specifically focusing on their antioxidant, anti-inflammatory, cytotoxicity and dermatoprotective effects. Antioxidant potential was evaluated using DPPH, FRAP and beta-carotene assays, with CS-EO and limonene exhibiting comparable efficacy. Anti-inflammatory properties were assessed via inhibition assays of prostaglandin E2 (PGE2) and nitric oxide (NO) production, showing significant reductions in LPS-stimulated macrophages treated by CS-EO or limonene. Cytotoxicity testing on various cell lines indicated selective activity of the tested compounds, with low toxicity observed on human skin fibroblasts. Limonene and CS-EO were highly effective on HepG2 cellules, with IC50 values of 0.55 ± 0.01 µg/mL and 15.97 ± 1.20 µg/mL, respectively. Dermatoprotective effects were further confirmed using enzymes, where CS-EO and limonene showed remarkable inhibitory potential against elastase (IC50 of 65.72 ± 1.92 and 86.07 ± 1.53 µg/mL, respectively) and tyrosinase (IC50 of 102 ± 2.16 and 78.34 ± 1.15 µg/mL, respectively) enzymes compared to quercetin used as a standard (IC50 of 111.03 ± 0.1 and 124.22 ± 0.07 µg/mL, respectively). Conclusions: The findings of this study suggest the potential for the development of new therapeutic approaches based on CS-EO, which could be applicable in the pharmaceutical, cosmetic and nutraceutical fields and have protective benefits for skin health.